Repetitive hydatidiform mole in the cesarean scar: a case report and literature review - G.L. Liu; S.C. He; W.J. Shan; H.Y. Chen (IMR Press, 2020)
Objective: To report a case of Repetitive hydatidiform mole in the cesarean scar. Case Report: a 35-year-old woman presented to our hospital with irregular vaginal bleeding for more than one month. Transvaginal ultrasonography, serum hCG confirmed the cesarean scar pregnancy. The patient underwent a bilateral uterine artery embolization and a suction evacuation. The postoperative histologic examination of the tissue revealed a hydatidiform mole. Molar pregnancy in the cesarean scar is tough to differentiate from a normal cesarean scar pregnancy with serum hCG or sonogram. It was necessary to perform a histological examination of the post operative specimen for the cesarean scar pregnancy. Conclusion: A high index of suspicion is needed for early diagnosis and management of cesarean scar molar pregnancy. If we ignore it, it can be challenging to manage and can have potentially catastrophic consequences.